Análise ergonômica do trabalho frente a pandemia de COVID-19 - Galvan, Isabela Caroline Gagliotto (2022)
The pandemic of COVID-19 is one of the most severe and long-lasting in recent times. One way to control the spread of the virus is the distancing of people and adoption of lockdown in various sectors. One of the first services to migrate to the remote regime was education at all levels, then office workers (such as designers, lawyers, accountants, among others) also adhered to home-office; however, service providers and commerce had their activities badly damaged by the lockdown and, gradually, their establishments are going through a flexibilization of service to the public. In this context, we can see a scenario in which the organization of work was remodeled, whether for the workers who started to work at home-office or for those who had to adapt their workstations in order to continue working, minimizing the risk of contamination with the coronavirus. To understand this new system, a Systematic Literature Review (SLR) was carried out using the Knowledge Development Process - Constructivist (ProKnow-C) method with the objective of building a conceptual model for ergonomic analysis, and to support the development of research protocols in cases: home-office service providers (teachers and software developers) and face-to-face service providers (machine shops and construction sites). The research protocols consist of the development and application of a questionnaire to employees and an audit in the on-site work environment. The proposition of a model for ergonomic assessment in times of pandemic is the theoretical contribution to the research, since the theme is recent. From a practical point of view, the survey of this data makes it possible to generate indicators of the quality of work, highlighting points of intervention that can improve the productivity and quality of life of workers, reducing losses, development of physical and mental health problems and minimizing the risk of contagion from COVID-19.